Minimally Invasive Spinal Arthrodesis in Osteoporotic Population Using a Cannulated and Fenestrated Augmented Screw: Technical Description and Clinical Experience. (30th August 2012) - Lubansu, Alphonse; Rynkowski, Michal; Abeloos, Laurence; Appelboom, Geoffrey; Dewitte, Olivier
Abstract : We describe a percutaneous or minimally invasive approach to apply an augmentation of pedicle fenestrated screws by injection of the PMMA bone cement through the implant and determine the safety and efficiency of this technique in a clinical series of 15 elderly osteoporotic patients. Clinical outcome and the function were assessed using respectively the Visual Analogue Scale (VAS) score and the Oswestry Disability Index (ODI). Peri- and post-operative complications were monitored during a minimum of 2 years of follow-up. Radiographic follow-up was based on plain fluoroscopic control at 3, 6 and 12 months and every year. In this approach, four steps were considered with care: optimal positioning of the screws, correct alignment of the screw heads, waiting time before the injection of cement, fluoroscopic control of the cement injection. Using these precautions, only 2 minor complications occurred. VAS scores and ODI questionnaires showed a statistically significant improvement up to 13.3 months postoperatively. No radiological complications were observed. Based on this experience, PMMA augmentation technique through the novel fenestrated screws provided an effective and long lasting fixation in osteoporotic patients. Applying this procedure through percutaneous or minimally invasive approach under fluoroscopic control seems to be safe.